Conservation and the genetics of populations - Allendorf, Frederick William; Luikart, Gordon (Malden, MA ; Oxford : Blackwell Pub., 2007)
"This book provides a thorough understanding of the genetic basis of biological problems in conservation. Conservation and the Genetics of Populations gives a comprehensive overview of the essential background, concepts, and tools needed to understand how genetic information can be used to develop conservation plans for species threatened with extinction." "Loss of biodiversity is among the greatest problems facing the world today, but thanks to new molecular technologies, statistical methods, and computer programs, genetic theories and methods are becoming increasingly useful in the conservation of biological diversity. Using a balance of data and theory, and basic and applied research, Conservation and the Genetics of Populations examines genetic and phenotypic variation in natural populations, the principles and mechanisms of evolutionary change, the interpretation of genetic data from natural populations, and how this may be applied to conservation. The book includes examples from both plants and animals, as well as from natural and captive populations." "This book is essential reading for advanced undergraduate and graduate students of conservation genetics, natural resource management, and conservation biology, as well as professional conservation biologists working for wildlife and habitat management agencies."--BOOK JACKET.
1. Introduction -- 2. Phenotypic variation in natural populations -- 3. Genetic variation in natural populations : chromosomes and proteins -- 4. Genetic variation in natural populations : DNA -- 5. Random mating populations : Hardy-Weinberg principle -- 6. Small populations and genetic drift -- 7. Effective population size -- 8. Natural selection -- 9. Population subdivision -- 10. Multiple loci -- 11. Quantitative genetics -- 12. Mutation -- 13. Inbreeding depression -- 14. Demography and extinction -- 15. Metapopulations and fragmentation -- 16. Units of conservation -- 17. Hybridization -- 18. Conservation breeding and restoration -- 19. Invasive species -- 20. Forensic and management applications of genetic identification -- App. Probability and statistics.
Includes bibliographical references (p. [577]-625) and index.
Keywords: Biodiversity conservation; Population genetics; Evolutionary genetics; Conservation of Natural Resources; Ecosystem; Ecology; Genetics, Population; Population Dynamics